Masjid Sri Alam Dunia dan Hubungannya dengan Penyebaran Islam di Sipirok, Tapanuli Selatan - Pasaribu, Ahmat Gunawan; Qorib, Ahmad; Muchsin, Kasron (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article discusses the history and contribution of the Sri Alam Dunia Grand Mosque in the spread of Islam in the Sipirok area, South Tapanuli. This study uses a qualitative research method with a historical approach. The historical approach has four writing steps, namely: heuristics, criticism, interpretation, and historiography. The Great Mosque of Sri Alam Dunia is a silent witness to the struggle of the Mandailing scholars in expanding the symbols of Islam in the South Tapanuli region. At first, the Sri Alam Dunia Mosque was a small surah that was used as a place to study religion. The central figures who contributed to the process of establishing this mosque were Sheikh Abdul Manan Siregar and the Muslims who live around the mosque. This mosque was built around 1926 AD and was completed in 1933 AD. The results of the research that the authors found were that the Sri Alam Dunia Mosque besides having a long history was also a socio-cultural center for the Sipirok community, both in ancient times and today. With these various functions, making the Sri Alam Dunia Mosque one of the icons of pride for Muslims in Sipirok.